Block precoding for MUI - Zhengdao Wang
Potential increase in capacity along with the need to provide multimedia services and cope with multiuser interference (MUI) and intersymbol interference (ISI) arising due to wireless multipath propagation, motivate well multirate wideband code-division multiple-access (CDMA) systems. Unlike most existing continuous-time symbol-periodic and multipath-free studies, the present paper develops an all-digital block-precoded filter-bank framework capable of encompassing single- or multirate transceivers for asynchronous or quasi-synchronous CDMA transmissions through multipath channels. Thanks to symbol blocking and through appropriate design of user codes, the resulting generalized multicarrier (GMC) CDMA system not only subsumes known multicarrier CDMA variants, but also equips them with flexible multirate capabilities. It is computationally simple, and guarantees symbol recovery regardless of the (possibly unknown) FIR multipath channels in both downlink and uplink setups. Simulations corroborate that the novel GMC-CDMA system outperforms existing multirate alternatives in the presence of asynchronism and multipath, and illustrate the feasibility of recovering blindly multirate transmissions received through unknown frequency-selective channels in the uplink. The performance of GMC-CDMA system in UMTS channels is also simulated and compared with existing multirate schemes
Keywords: DS-CDMA.; FIR multipath channels; GMC-CDMA system; MUI/ISI-resilient generalized multicarrier CDMA; UMTS channels; All-digital block-precoded filter-bank.; Asynchronous CDMA transmission; Blind equalization; Block precoding; Downlink; Frequency-selective channels; Intersymbol interference; Multimedia services; Multirate transceivers; Multirate wideband code-division multiple-access.; Multiuser interference; Quasi-synchronous CDMA transmission; Simulations; Single-rate transceivers; Symbol blocking; Symbol recovery; System capacity; Uplink; User codes design; Wireless multipath propagation